Zoning of the Lower Volga Region and Formation of Territory, Okrug, District and Rural Bodies of Soviet Authority in 1928: First Stage - Ekaterina Furman (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The article examines the process of formation of the Lower Volga region and Soviet authorities at the level of regional, district, and rural administration at the first stage of zoning (before the liquidation of okrugs). Methods and materials. The research was carried out based on traditional methods of historical research (historical-genetic, retrospective, historical-systemic, and historical-comparative). The use of an array of unpublished archival documents stored in the State Archives of the Volgograd Region and the Documentation Center for Contemporary History of the Volgograd Region, and materials from periodicals and legislative sources of government bodies of the USSR and the RSFSR, greatly facilitated the research process. Analysis. The study is aimed at identifying the regional specifics of the zoning process and the accompanying process of formation of Soviet authorities (at the level of councils and executive committees of councils of the Lower Volga region). Results. The zoning of the Lower Volga region already at the first stage revealed a range of problems, the systematic solution of which in the future will make it possible to transform the agricultural region into the industrial center of the Volga region. In the process of reform, along with positive aspects – the reduction in cost of the management apparatus, the bringing closer to the population of Soviet authorities endowed with significant powers (district executive committees and councils) – there were also clearly negative consequences. The distance of rural councils from middle management and the consolidation of individual rural councils, on the one hand, led to the planned reduction of hardware costs but, on the other hand, excluded remote villages from active public life. Districts became the main operational unit of economic and Soviet work in the region. There were several issues to address, including the imbalance between districts with different population sizes, from small ones with just over 2,000 people to large ones with populations approaching 100,000. Additionally, there was a lack of communication between administrative units and personnel problems, which emerged as a significant hurdle in the development of district and rural Soviet administration at the second stage of zoning (in the conditions of the liquidation of okrugs).